2019
DOI: 10.1111/syen.12404
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the family Coccidae (Hemiptera, Coccomorpha), with a discussion of their waxy ovisacs

Abstract: Coccidae is one of the major families of scale insects, with many species considered to be serious agricultural or horticultural pests. However, the phylogenetic relationships among coccid subfamilies, tribes and genera are poorly understood because existing hypotheses are based on morphological characters and cladistic analyses. Here, we present the first molecular phylogeny of the family Coccidae based on DNA fragments of a mitochondrial gene (COI), nuclear ribosomal RNA genes (18S and 28S), and elongation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…The result showed that the monophyly of Coccoidea was highly supported and Ceroplastes japonicus Green, 1921 was the sister group of S. coffeae. This may imply the Ceroplastinae and Coccinae have a closer relationship related to the Eulecaniinae represented by D. koreanus, consistent with the current result based on multiple molecular markers (Choi and Lee 2020).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The result showed that the monophyly of Coccoidea was highly supported and Ceroplastes japonicus Green, 1921 was the sister group of S. coffeae. This may imply the Ceroplastinae and Coccinae have a closer relationship related to the Eulecaniinae represented by D. koreanus, consistent with the current result based on multiple molecular markers (Choi and Lee 2020).…”
supporting
confidence: 90%
“…And many coccid species are economically significant insects in agriculture, horticulture, and forestry ( Miller and Davidson 1990 ; Miller et al 2005 ). But understanding of the phylogenetic relationships within this family remains limited because the taxonomy on the Coccidae is based largely on the morphological characters from the female adult (Gullan and Cook 2007 ; Choi and Lee 2020 ). In this study, the complete mitochondrial genome of Didesmococcus koreanus Borchsenius, 1955 was reported and the phylogenetic relationship was reconstructed combined with other two coccid species and other 17 hemipteran species (Deng et al.…”
mentioning
confidence: 99%
“…Within Coccidae, the topology of ML and the Bayesian tree was largely similar, except for the Aclerdidae nested in Coccidae in the Bayesian tree. The Ceroplastinae represented by C. floridensis and C. japonicus had a closer affinity with Coccinae, represented by P. nigra and S. coffeae in both ML and Bayesian tree, then grouped with Eulecaniinae, represented by D. koreanus , corresponding with the topology (Eulecaniinae + (Coccinae B + Ceroplastinae)) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also describe how to separate the closely related genus Protopulvinaria and include a key to separate all four species assigned to the genus Milviscutulus. Molecular techniques for species identification have also been developed and GenBank contains gene nucleotide sequences for M. mangiferae (Yokogawa and Yahara, 2009;Lin et al, 2013;Gomez-Polo et al, 2017;Choi and Lee, 2019).…”
Section: Adultmentioning
confidence: 99%
“…Molecular techniques for species identification have also been developed and GenBank contains gene nucleotide sequences for M. mangiferae (Yokogawa and Yahara, 2009; Lin et al, 2013; Gomez‐Polo et al, 2017; Choi and Lee, 2019).…”
Section: Pest Categorisationmentioning
confidence: 99%